Effect of natural products on host cell autophagy induced by Influenza A virus infection - Liu, Xiaopan; Wang, Qingsen (Frontiers in Cellular and Infection Microbiology, 2024)
Influenza A virus (IAV) can cause seasonal epidemics and global pandemics, posing serious threats to public health, making a deeper understanding of its biological characteristics and effective countermeasure strategies essential. Autophagy not only maintains cellular homeostasis but also plays an important role in host defense against IAV infection. However, the relationship between IAV and autophagy is complex, and effective antiviral drugs are not yet available. Natural products have shown excellent potential in disease control due to their diversity and multi-targeting. This review focuses on the relationship between IAV and autophagy and discusses the potential of targeting autophagic pathways for the development of new antiviral therapies. Particularly, the use of plant extracts as autophagy modulators has garnered attention due to their non-toxic nature and cost-effectiveness, which provides strong support for the development of future antiviral drugs that can help to inhibit viral infections and slow down disease progression.